PROPERTY RIGHTS AND THE BASIC STRUCTURE OF THE CONSTITUTION: THE CASE OF THE DRAFT CONSTITUTION EIGHTEENTH AMENDMENT BILL (The Pretoria Student Law Review, 2021)
The land reform debate in South Africa has always been as contentious as it is controversial. Up to now, however, it has not reached the intensity of bringing about changes to South Africa’s fundamental law. In February 2018, Parliament resolved in favour of adopting an amendment to the Constitution that would allow government to expropriate private property without being required to pay compensation.1 This began a process that eventually culminated in the December 2019 publication of the draft Constitution Eighteenth Amendment Bill. This is the first time since the Constitution was enacted that an amendment has been introduced to change a provision in chapter 2, in this case section 25. The basic structure doctrine is a judicial doctrine that features most prominently but not exclusively in the constitutional law of India.2 The doctrine’s essence is that constitutional amendments, despite complying with the formal requirements for amendment set out in the constitutional text, might still be struck down by a court because the amendment offends the constitution’s foundational principles, its identity, character, or logic — its basic structure.3 In 2005, Devenish wrote that the basic structure doctrine has been implicitly recognised by the Constitutional Court as applicable in South Africa, but that ‘the doctrine is waiting in the wings, since, should certain circumstances and a crisis situation arise, the Constitutional Court could invoke its application’.4 At the time of Devenish’s writing, there was no pending amendment of the Bill of Rights, unlike today. In this paper, I briefly summarise the amendment procedure set out in section 74 of the Constitution, and the process that has taken place between February 2018 and June 2020. Thereafter, I briefly discuss the basic structure doctrine and its potential application in South Africa. Finally, I consider whether the basic structure doctrine could be employed as a viable challenge to the draft Constitution Eighteenth Amendment Bill. The question that is inevitably considered: Has the crisis, that Devenish referred to, arrived?
Keywords: land reform debate; South Africa; Constitutional Court